Pulling back the curtain on qualitative research - Thompson, William E. (William Edwin), 1950- author.
1 online resource.
Keywords: "In Pulling Back the Curtain on Qualitative Research, the authors maintain that for sociologists the entire world is a laboratory. Seldom do they attend social gatherings without observing people and their interaction in a systematic and intellectually curious way. Regular trips to the grocery store, church services, and engagement with social media all open the door to sociological questioning and encourage forms of empirical observation and data collection. Here, in this practical and in-depth guide to conducting qualitative sociological field research, the authors offer step-by-step guidance to the processes of choosing a research question and forming research objectives; gaining entry to research settings; and reporting and analyzing findings. Each chapter centers a past research assignment, wherein the authors draw attention to important ethical considerations and extract the many lessons, quirks, and unanticipated findings they experienced along the way that readers should prepare for and apply while conducting their own qualitative fieldwork. Over the span of several field studies, this book offers readers a behind-the-scenes look at some tested and trusted qualitative methodologies. Designed to be a guide for undergraduate and graduate level students, its real-life meditations would make a meaningful addition to anyone serious about conducting sociological research"--